Renewable energy generation system connected to micro grid and analysis of energy management: a critical review - Pranita Rathod; Sanjoy Kumar Mishra; Sujit Kumar Bhuyan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Renewable energy generations have been employed throughout the world in order to meet the increasing load demand. It is a pollution free and abundantly accessible. The generation cost has been reduced because of more research advancement. Photovoltaic (PV) can’t generate throughout the day due to weather condition. In order to maintain the continuity of power generation a hybrid renewable generation system (HRGS) concept has been considered in this research work. HRGS is an integration of more than one renewable energy which consists of PV, wind, solid oxide fuel cell (SOFC), an auxiliary unit (AU). AU is used as a backup generation which can generate power when all the renewable energy fails to generate. AU may be of diesel generator (DG) or super capacitor. This paper discusses the various parts of HRGS and its comparison. Furthermore, its impact of energy management so as to deliver the energy to the grid in a continuous and reliable manner. Therefore, a detail study of different component of HRGS & renewable energy has been highlighted which will be helpful for the new researchers for advancement of power generation and its control strategy of energy management connected to the grid.